A protocol for developing reporting guidelines for laboratory studies in Endodontology. (25th April 2019) - Nagendrababu, V.; Murray, P. E.; Ordinola‐Zapata, R.; Peters, O. A.; Rôças, I. N.; Siqueira, J. F.; Priya, E.; Jayaraman, J.; Pulikkotil, S. J.; Dummer, P. M. H.
Abstract: Laboratory‐based research studies are the most common form of research endeavour and make up the majority of manuscripts that are submitted for publication in the field of Endodontology. The scientific information derived from laboratory studies can be used to design a wide range of subsequent studies and clinical trials and may have translational potential to benefit clinical practice. Unfortunately, the majority of laboratory‐based articles submitted for publication fail the peer‐review step, because unacceptable flaws or substantial limitations are identified. Even when apparently well‐conducted laboratory‐based articles are peer‐reviewed, they can often require substantial corrections prior to the publication. It is apparent that some authors and reviewers may lack the training and experience to have developed a systematic approach to evaluate the quality of laboratory studies. Occasionally, even accepted manuscripts contain limitations that may compromise interpretation of data. To help authors avoid manuscript rejection and correction pitfalls, and to aid editors/reviewers to evaluate manuscripts systematically, the purpose of this project is to establish and publish quality guidelines for authors to report laboratory studies in the field of Endodontology so that the highest standards are achieved. The new guidelines will be named–'Preferred Reporting Items for Laboratory studies in Endodontology' (PRILE). A steering committee was assembled by the project leads to develop the guidelines through a five‐phase consensus process. The committee will identify new items as well as review and adapt items from existing guidelines. The items forming the draft guidelines will be reviewed and refined by a PRILE Delphi Group (PDG). The items will be evaluated by the PDG on a nine‐point Likert scale for relevance and inclusion. The agreed items will then be discussed by a PRILE face‐to‐face consensus meeting group (PFCMG) formed by 20 individuals to further refine the guidelines. This will be subject to final approval by the steering committee. The approved PRILE guidelines will be disseminated through publication in relevant journals, presented at congresses/meetings, and be freely available on a dedicated website. Feedback and comments will be solicited from researchers, editors and peer reviewers, who are invited to contact the steering committee with comments to help them update the guidelines periodically.